The planning model of dairy farm - Irma Skarulskienė (Lietuvos Matematikos Rinkinys, 2004)
The optimal plan creation for each year of three years period and manufacture prognostication mathematical model, which evaluates the relations between plant growing and stockbreeding, is presented. Described model allows counting of the plant growing and stockbreeding manufacturing volumes, the farm direct expenses, and marketable production. The direct programming method is used for finding of maximized benefit.